The effect of light on the oxidative stability of palm olein - Ghazali, Z.; Wan Nik, W. B.; Ku Bulat, K. H.; Ani, F. N.; Xian, L. F. (2006)
The effect of light and additives on the oxidative stability of palm olein has been studied. Acid value, peroxide value and iodine value of the oil samples at selected hours were evaluated in this study. The micro structural changes of palm olein were confirmed by using Fourier transform infrared (FTIR) spectroscopy while thermogravimetric analysis (TGA) was used in order to detect any changes in the bulk properties of palm olein. It was found that the effect of light and heat can increase the lipid oxidation. Palm olein blended with the additive Irgalube F10 showed lower acid values compared to original palm olein after 768 hours of heating. Addition of additive Irgalube F10 in oil samples is able to increase the thermal oxidation stability.